Does bank competition and concentration lead to financial stability? - JOVI, DACANAY (Archīum Ateneo, 2017)
This study verifies the "competition-fragility" and the "competition-stability" views in the context of imperfect competition and a binding bank capitalization regulatory constraint in the banking industry of the Philippines. With this current environment